Forest damage - Hantula, Jarkko; Elfstrand, Malin; Hekkala, Anne-Maarit; Hietala, Ari M.; Honkaniemi, Juha; Klapwijk, Maartje; Koivula, Matti; Matala, Juho; Rönnberg, Jonas; Siitonen, Juha; Widemo, Fredrik (Springer, 2025)
Heterobasidion root and butt rot pose a greater risk in continuous cover forestry (CCF) than in rotation forestry (RF) in conifer-dominated forests, regardless of whether selective, gap or shelterwood cutting is used. Damage from wind, snow, spruce bark beetle, and large pine weevil are likely to be less severe in CCF than in RF. However, the conversion of RF to CCF may briefly expose stands to windthrow. Browsing by large herbivores on saplings may limit regeneration of tree species other than spruce in continuous cover forestry and reduce tree species diversity, but alternative silvicultural practices may also increase forage availability in the field and shrub layer. Browsing damage outcomes for saplings in CCF are difficult to predict. For many types of damage in CCF, substantial knowledge gaps complicate the assessment of damage risk.
Keywords: abiotic damage; Heterobasidion root rot; forest disease; European spruce bark beetle; cervid damage